2006
DOI: 10.1016/j.clinbiochem.2005.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and antioxidant status in non-metastatic prostate cancer and benign prostatic hyperplasia

Abstract: Objectives: We undertook the present study to investigate the possible alteration of oxidant/antioxidant status in the circulation of patients with prostate cancer and benign prostatic hyperplasia.Design and methods: Thiobarbituric acid reactive substances (TBARS), the enzyme activities of superoxide dismutase (SOD), glutathione peroxidase (GPX), catalase (CAT) and copper (Cu) and zinc (Zn) levels were estimated in the erythrocytes of 25 non-metastatic prostate cancer patients, 36 benign prostatic hyperplasia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
172
2
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 192 publications
(194 citation statements)
references
References 25 publications
9
172
2
11
Order By: Relevance
“…Haeme oxygenase-1 may therefore be one guardian of the genome, limiting mutations of DNA and promoting deletion of aberrant cells (Oates and West, 2006). An altered prooxidant/antioxidant balance in PCa patients, reflected by elevated lipid peroxidation and concomitant antioxidant depletion, was suggested to lead to an increase in oxidative damage playing an important role in prostate carcinogenesis (Yilmaz et al, 2004;Aydin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Haeme oxygenase-1 may therefore be one guardian of the genome, limiting mutations of DNA and promoting deletion of aberrant cells (Oates and West, 2006). An altered prooxidant/antioxidant balance in PCa patients, reflected by elevated lipid peroxidation and concomitant antioxidant depletion, was suggested to lead to an increase in oxidative damage playing an important role in prostate carcinogenesis (Yilmaz et al, 2004;Aydin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In BPH, increased lipid peroxidation and decreased levels of antioxidants have been observed. [23][24][25] Various herbal extracts reduce oxidative stress in testosterone-induced BPH rats. [26][27][28][29] In addition, saw palmetto extract, which is commonly used to treat BPH, has shown antioxidant effects.…”
mentioning
confidence: 99%
“…11 Aydin et al conducted a controlled study to evaluate antioxidant activity in the patients with PCa and BPH and revealed that PCa patients had decreased CuZn-SOD enzyme levels when compared with BPH and control. 21 Jun-Fu Zhou et al also demonstrated significantly decreased CuZn-SOD levels in chronic bacterial prostatitis (category 3), but the literature data regarding AIP patients is lacking. 22 In our study, decreased CuZn-SOD enzyme levels were found to be lower in PCa and BPH patients, but these differences were statistically significant only for BPH and control group patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors demonstrated decreased activity while others showed no difference or increased activity. 21,[23][24][25] In their study, Biri et al reported increased CAT and GPx activity in PCa patients when compared with BPH and control. 25 They concluded that this increase was due to a rebound effect to increased oxidative stress in order to neutralize it.…”
Section: Discussionmentioning
confidence: 99%